Pengukuran Dan Analisis Produktivitas Menggunakan Metode Objective Matrix (Omax) di Unit Produksi Workshop Putar PT Xyz - Vina Sabrina; Rizqi Novita Sari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Productivity is an indicator of a company's performance. In 2021 to 2023, a precast concrete construction and manufacturing company had difficulty achieving its spun pile production target of 3,480 tons/month. This condition causes the company's productivity to fluctuate and tend to decrease overall. This study aims to evaluate the decline in productivity by measuring the value of productivity based on 3 criteria, namely material, labor and machine criteria. The method used is Objective Matrix (OMAX). The productivity value in the production years 2021 to 2023 fluctuates with a downward average value. The highest productivity value in the 2021 production year occurred in period 8 with a value of 748 while the lowest productivity value occurred in period 6 with a value of 170. The highest productivity value in the 2022 production year occurred in period 21 with a value of 638 while the lowest productivity value occurred in period 14 with a value of 166. The highest productivity value in production year 2023 occurs in period 26 with a value of 966 while the lowest productivity value occurs in period 27 with a value of 0. Criteria that contribute less to productivity and need to be improved are labor criteria that show values below the average. While the material and machinery criteria show values that tend to be below average. While the material and machine criteria show values that tend to be good, with the application of OMAX, PT XYZ can improve partial productivity and total productivity in the future and identify factors that cause a decrease in productivity.